Kejelasan Fonetik dalam Pengucapan Bahasa Jerman dan Bahasa Indonesia - Nengsih Silviana; Frensy Sefriana; Kristin Simanjuntak; Ruth Krenia; Nurul Azizah (Jurnal Bintang Pendidikan Indonesia, 2025)
Phonetics has an important role in clarifying the pronunciation of a language, including in German and Indonesian. These two languages have different phonetic systems, which can affect clarity and understanding in oral communication. This study aims to analyze the phonetic differences between German and Indonesian in terms of vowels, consonants, word stress, and intonation. Using the comparative analysis method, this study examines data from various academic sources as well as direct observation of German and Indonesian learners. The results show that the differences in the vowel and consonant systems present challenges for learners in mastering clear and precise pronunciation. In addition, word stress and intonation in German have a significant influence on meaning, while in Indonesian, pronunciation tends to be flatter and does not experience much change in meaning due to stress differences. This study emphasizes the importance of understanding phonetics in language learning to improve effective speaking skills.